THE EFFECTIVENESS OF SPAYLATER USAGE IN SHOPPING ACTIVITIES DURING COVID-19 PANDEMIC: (Case Study on Tasikmalaya City Community) - Sri, Fuji Dewi; Rahmawati, Anisa (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2022)
This study aims to determine the level of satisfaction with the use of e-wallet (Shopee Pay) as a non-cash payment instrument. The research method used is descriptive qualitative research. The technique of collecting data is by means of a survey in the form of a questionnaire instrument which is then distributed via google form. Simple random sample was used as a sampling technique of 80 respondents. SPayLater is an online shopping platform that aims to facilitate the online shopping process for Shopee users. SPayLater is a payment method that uses bailout funds from the application company in question. SPayLater offers loan products with a 0% initial loan without a minimum transaction. However, we are encouraged to realize the risks that may occur behind this convenience, and this feature might be described as a teaser in the millennial period.